Digitalisasi Administrasi Kelulusan melalui Pembuatan Sistem Informasi Kelengkapan Dokumen Yudisium Berbasis Web pada Program Studi Teknik Informatika Politeknik Negeri Cilacap - Annisa Gatri Zakinah; Cahya Vikasari; Nur Muniroh (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2026)
The graduation administration process in the Informatics Engineering Study Program at Cilacap State Polytechnic is still manual, which often leads to incomplete student documents and errors in graduation (yudisium) reporting. This community service activity aims to digitize graduation administration by developing a web-based information system for managing graduation document completeness, accessible to the Study Program Coordinator and department admins. The method used is participatory action research with five stages: needs analysis consultation, system design, application development, user testing, and socialization/training. The system was successfully developed with features including student data management, an auto-save checklist of 8 documents, upload of approval forms, automation of graduation eligibility status, a statistical dashboard, and exportable reports. Testing showed that 100% of scenarios were successful. Socialization was conducted online for the Head of Study Program and two department admins. Document verification time decreased from 5 minutes to 30 seconds per student, human error regarding false completeness declarations was eliminated, and eligible data recaps became real-time. The digitization of graduation administration successfully improved the accuracy, efficiency, and accountability of graduation services. The system is recommended for official implementation and expansion to other study programs.